Analisis Profil Kompetensi Digital dan Profesionalisme Guru PAI dalam Menghadapi Transformasi Pendidikan Digital - Putri Natasya; sabila dwi; Moh Faizin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the profile of digital competence and professionalism of Islamic Religious Education (PAI) teachers in facing digital transformation in education. This research is motivated by the changing role of teachers in the digital era, where teachers are no longer merely knowledge transmitters but also facilitators, innovators, and filters of religious information in digital spaces. This study employs a qualitative approach using a library research method. Data were collected from various scientific sources, including journals, books, and previous research related to digital competence, teacher professionalism, and digitalbased Islamic education. The data were analyzed using a descriptive-critical approach to identify key patterns and issues. The findings reveal that the digital competence of PAI teachers includes not only technical skills but also the ability to integrate technology into pedagogical practices (TPACK), digital literacy, and the use of interactive learning media. Teacher professionalism in the digital era is reflected in adaptability to technological developments, the application of Islamic-based digital ethics, and the role of teachers as guides in filtering religious information. However, several challenges persist, including low digital literacy, limited infrastructure, resistance to change, and difficulties in transforming spiritual values into digital learning contexts. This study is limited to a conceptual and literature-based analysis without direct empirical data. Therefore, future research is recommended to conduct empirical studies to examine the implementation of digital competence and professionalism of PAI teachers in various educational contexts.